2022
DOI: 10.1002/vetr.1378
|View full text |Cite
|
Sign up to set email alerts
|

Use of health parameter trends to communicate pet health information in companion animal practice: A mixed methods analysis

Abstract: Background Reviewing patient health parameter trends can strengthen veterinarian–client–patient relationships. The objective of this study is to identify characteristics associated with veterinarians’ communication of health parameter trends to companion animal clients. Methods Using a sequential exploratory mixed methods design, independent pet owner (n = 27) and veterinarian (n = 24) focus groups were conducted and analysed via content analysis to assess perceptions of how health parameter trends are communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Advocates have promoted the importance of preventing pet obesity, 38 and the use of trends has been identified as an integral component of preventive veterinary care 39 . A recent investigation of the use of trends in companion animal practice found that the majority of trends discussed by veterinarians with clients focused on pet weight, although most were retrospective or retrospective and prospective, indicating a lack of proactive monitoring of pets’ weight trends 40 . The findings support further encouraging veterinary professionals to focus on the importance of maintaining a healthy bodyweight when the pet is still at a healthy weight, as well as educating clients on the importance of pets’ weight in relation to their overall health from early in life and over their lifetime.…”
Section: Discussionmentioning
confidence: 99%
“…Advocates have promoted the importance of preventing pet obesity, 38 and the use of trends has been identified as an integral component of preventive veterinary care 39 . A recent investigation of the use of trends in companion animal practice found that the majority of trends discussed by veterinarians with clients focused on pet weight, although most were retrospective or retrospective and prospective, indicating a lack of proactive monitoring of pets’ weight trends 40 . The findings support further encouraging veterinary professionals to focus on the importance of maintaining a healthy bodyweight when the pet is still at a healthy weight, as well as educating clients on the importance of pets’ weight in relation to their overall health from early in life and over their lifetime.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, monitoring trends in pet health parameters has been promoted as an important aspect of preventive veterinary care, 19 yet recent research with the same study population has indicated that participating veterinarians' use of trends to communicate with clients is very limited. 20 Increased use of trends within veterinarian-client interactions may help identify the need for early intervention to maintain a healthy pet weight. Pet obesity advocates highlight that prevention of pet obesity is easier than trying to achieve weight loss followed by weight maintenance over the longterm.…”
Section: Discussionmentioning
confidence: 99%
“…16 Furthermore, although visual aids such as graphs and tables have previously been identified as positive adjuncts for the discussion of health trends, 17 they were rarely used in these consultations. 16 As in previous studies evaluating preventive healthcare consultations, [18][19][20] the primary reason cited for these disparities between expectations and actual practice was that the time allocated for routine consultations is typically too short to allow for complex discussions. 16 In addition, poor availability of software to display trends from clinical records, limited access to visual displays of normal data and the costs associated with repeated laboratory tests were also identified as barriers to the discussion of health parameter trends.…”
Section: What You Need To Knowmentioning
confidence: 99%
“…Despite both veterinarians and clients expressing a desire to discuss trends in clinical and laboratory parameters, such discussion was absent in 90 per cent of the consultations observed in this study. 16 Furthermore, although visual aids such as graphs and tables have previously been identified as positive adjuncts for the discussion of health trends, 17 they were rarely used in these consultations. 16 As in previous studies evaluating preventive healthcare consultations, [18][19][20] the primary reason cited for these disparities between expectations and actual practice was that the time allocated for routine consultations is typically too short to allow for complex discussions.…”
Section: What You Need To Knowmentioning
confidence: 99%
See 1 more Smart Citation